Batavia dalam Rongrongan Kolonialisme Belanda Melalui VOC Abad ke XVII – XIX - Sabrina, Dewi Ayu; Utami, Aditya Putri; Aman; Basyari, Asyhar (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
Writing in this journal aims to find out the history of the arrival of the Dutch until the formation of the city of Batavia. Starting with the arrival of the Dutch in 1595 with a mission to explore the Ocean to Banten, this was the beginning of colonialism in Indonesia. The Dutch founded the VOC (Verenigde Oost Indische Compagnie) on 20 March 1602 in Batavia as an administrative center. All VOC activities were centered in Batavia before being headquartered in Banten. The choice of Batavia or its former name Jayakarta as the administrative center was because the Dutch saw that the port in Batavia was a small port so it would not easily attract the attention of other European nations. Writing articles uses a library research approach, where the preparation of articles uses literary sources and does not go directly to the field. The results of the discussion in this article include, Batavia as the VOC Headquarters, the state of the VOC under Daendels' rule after the dissolution of the VOC, Batavia as a port and trade city. Penulisan jurnal ini bertujuan untuk mengetahui sejarah kedatangan Belanda hingga terbentuknya kota Batavia. Diawali dengan Kedatangan Belanda pada 1595 dengan misi penjelajahan Samudra ke Banten merupakan awal kolonialisme di Indonesia bermula. Belanda mendirikan VOC (Verenigde Oost Indische Compagnie) pada 20 Maret 1602 di Batavia sebagai pusat administrasi. Segala kegiatan VOC dipusatkan di Batavia sebelum dulunya bermarkas di Banten. Pemilihan Batavia atau nama dulunya Jayakarta sebagai pusat administrasi ini karena Belanda melihat pelabuhan yang ada di Batavia merupakan pelabuhan kecil sehingga tidak mudah menarik perhatian bangsa Eropa lainnya. Penulisan artikel menggunakan metode pendekatan penelitian kepustakaan (library research), dimana penyusunan artikel menggunakan sumber literatur dan tidak terjun langsung ke lapangan. Hasil pembahasan dalam artikel ini antara lain, Batavia sebagai Markas Besar VOC, Keadaan VOC di bawah pemerintahan Daendels pasca bubarnya VOC, Batavia sebagai kota pelabuhan dan perdagangan.